Fock-Sobolev Spaces and Weighted Composition Operators among Them (Communications in Mathematical Research, 2021)
We characterize the boundedness and compactness of weighted composition operators among some Fock-Sobolev spaces. We also estimate the norm andessential norm of these operators. Furthermore, we discuss the duality spaces of Fock-Sobolev spaces $\mathcal{F}^{p,m}_s$ when $0 < p < ∞$.